Who really won the FIFA 2014 Golden Ball Award?: What sports can learn from multi-criteria decision analysis. (2016) - Mu, Enrique
The Golden Ball Award is given to the best soccer player in every FIFA World Cup tournament. Although disagreements will inevitably arise when any award winner is selected, we propose that an analytic hierarchical process (AHP) approach, which is taken from the toolbox of multi-criteria decision analysis (MCDA), be used for the purpose of selecting the Golden Ball winner. A review of the use of MCDA approaches within the sports management literature brought us to the conclusion that their use is still incipient in the scholarship within this community. AHP is proposed for the development of award evaluations because it is intuitive, accurate, and provides decision transparency to the public. The method is applied to the 2014 FIFA Golden Ball selection for illustration purposes and potential 2014 World Cup winners are suggested based on attack, defence, and fair play performance. Most importantly, the use of this proposed approach can be extended to the assessment of other sports awards.